Close quarters with the bodyguard - Childs, Lisa (Childs, Lisa. Bachelor bodyguards., 2021)
"Although her life is threatened, prosecutor Jocelyn Gerber insists she doesn't need protection. So she bristles at having bodyguard Landon Myers's presence forced on her. Jocelyn and Landon immediately share a mutual dislike and mistrust...with a strong undercurrent of sexual tension. When Landon rescues Jocelyn time and again, her heart begins to thaw...even as a criminal makes her the ultimate target"--